FALSAFAH KURIKULUM DALAM PENDIDIKAN ISLAM - Marzuki, Bakri (Hunafa: Jurnal Studia Islamika, 2008)
One of the operational components of Islamic education as a system is education material that is the entire learning materials taught to students in the Institutional System of Education. Education material, which is more popularly called curriculum, will continually change because of the change and development of thought of human beings. Therefore, to anticipate the change, a skill in curriculum development is extremely needed. In other words, the Islamic Education Institution must be able to anticipate the problem without forgetting the essence of the Islamic teachings themselves. Within this context, the main aspect that must be paid close attention to in designing the Islamic education institution is to make a change in cognitive, psychomotor, and affective aspects amongst students.Kata Kunci : falsafah kurikulum, pendidikan Islam